THE IMPORTANCE OF MARKETING SERVICES IN ASSESSING THE FINANCIAL STATE OF ENTERPRISES - Jurabayev Jurabek Mukhibillo ugli (Scholar Express Journals, 2025)
The article provides recommendations on the content of marketing services, the formation of their theoretical foundations, the importance of business entities in market activities, and the establishment of research work on the development of marketing services in Uzbekistan
Keywords: Marketing; Marketing Service; Marketing Service Object